Proceedings of the ACM Symposium on Applied Perception 2014
DOI: 10.1145/2628257.2628273
|View full text |Cite
|
Sign up to set email alerts
|

Minication affects action-based distance judgments in oculus rift HMDs

Abstract: Distance perception is a crucial component for many virtual reality applications, and numerous studies have shown that egocentric distances are judged to be compressed in head-mounted display (HMD) systems. Geometric minification, a technique where the graphics are rendered with a field of view that larger than the HMD's field of view, is one known method of eliminating the distance compression [Kuhl et al. 2009;Zhang et al. 2012]. This study uses direct blind walking to determine how minification might impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
(29 reference statements)
1
19
0
1
Order By: Relevance
“…However, none of those cues is singularly responsible for the underperception that characterizes distance perception in VEs. Recent research using newer HMDs has reported nearveridical judgments of egocentric distance (Li, Zhang, & Kuhl, 2014;Young, Gaylor, Andrus, & Bodenheimer, 2014), but the reason for the reported differences between HMDs is unknown. Distance judgments in the VE conditions of Li et al (2013;experiment 2) were larger than those in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
“…However, none of those cues is singularly responsible for the underperception that characterizes distance perception in VEs. Recent research using newer HMDs has reported nearveridical judgments of egocentric distance (Li, Zhang, & Kuhl, 2014;Young, Gaylor, Andrus, & Bodenheimer, 2014), but the reason for the reported differences between HMDs is unknown. Distance judgments in the VE conditions of Li et al (2013;experiment 2) were larger than those in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Research on perception of distance indicates that perceived distance is foreshortened in virtual compared to real environments (see Renner et al (2013) for a review), although this difference is narrowing with more modern displays (Buck et al 2018;Creem-Regehr et al 2015;Li et al 2014;Kelly et al 2017). Perception-action couplings have also been studied in the context of virtual environments (Kuhl et al 2008;Mohler et al 2007), but none to our knowledge have directly compared such couplings in matched real and virtual environments.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods use a "computer vision" approach applying perspective projection adjustments: Minification is a method which compresses the imaginary to artificially increasing the FOV of a display, and its application can improve distance perception ( [8], [28], [10]). Lowering the horizon is another similar method which had good results ( [14], [19]).…”
Section: Methods To Approximate Spatial Performancementioning
confidence: 99%